PERBANYAKAN KLON LADA VARIETAS PANNIYUR SECARA IN VITRO - YELNITITIS, YELNITITIS; BERMAWIE, NURLIANI; Syafaruddin, SYAFARUDDIN (Pusat Penelitian dan Pengembangan Perkebunan, 1999)
Multiplication ofpepper clone variety Panniyur in vitroThe study was conducted to determine effect of Benzyl Adenine (BA) on shoot multiplication and regeneration capacity of callus fom vaiety Panniyur. This esearch was undertaken at the Laboratory of Plant Genetic Resources and Beeding from Apil to October 1998. Nodal segment was used as explant source, taken from plantlet already gown on Murashige and Skoog (MS) medium. The expeiment was divided into two steps, shoot multiplication and regeneration of callus. The BA concentration used for shoot multiplication was 0.3, 1.0, 1 .5, 2.0. 2.5,3.0. and 5.0 mg/1 while for callus regeneration was 0.3. 0 5, and 0.7 mg/1. The expeiment was designed as completely randomized with 10 and 6 replications, respectively. Results showed thai the treatment with BA 2.5 mg/1 appeared to be the best medium for shoot multiplication indicated by the highest number of shoot, number of leaves and shoot height as much as 10.3, 5.6. and 4.40 cm in eight weeks, respectively. Culture performance from such culture was also the best with green leaves, fesh and vigorous. Addition of BA 0.7 mg/1 onto regeneration medium also the best treatment for shoot egeneration fom callus with average number of shoot 8.67. From such treatment was also obtained the highest growth rate with 4.35 cm shoot height and culture performance showing green leaves, average size and vigorous.